Anti-poisoning catalyst as well as preparation method and application thereof
By uniformly dispersing inorganic oxides on the nanoconductive support and loading precious metal alloys, the problem that platinum-based catalysts are easily toxic to CO and H2S is solved, and the anti-toxicity and catalytic activity of the catalyst is significantly improved.
Patent Information
- Application Number
- CN202411915982.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-18
AI Technical Summary
The platinum-based catalyst used in existing hydrogen fuel cells is easily toxic to impurity gases such as CO and H2S, resulting in the deactivation of the catalyst, limiting the commercial application of hydrogen fuel cells.
By adopting a one-step hydrothermal synthesis method, the inorganic oxide is uniformly dispersed on the nanoconductive support to form a composite support, and the precious metals and/or precious metal alloys are loaded thereon to improve the anti-toxicity performance of the catalyst.
The good anti-CO and H2S toxicity properties of the catalyst are achieved, and the catalytic activity and current retention rate of the hydroxide reaction are significantly improved, which is better than that of commercial Pt/C catalysts.
Smart Images

Figure CN119650732A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a fuel cell catalyst and a carrier thereof, belonging to the technical field of catalyst preparation. Background Art
[0002] A fuel cell is a device that converts chemical energy directly into electrical energy. When hydrogen is used as fuel, it is called a hydrogen fuel cell. Hydrogen fuel cell technology is becoming increasingly mature and is already in the early stages of commercial application. It has been applied to electric bicycles, mobile power sources, logistics vehicles, passenger cars, heavy trucks, ships, power stations, etc.
[0003] The commercialization of hydrogen fuel cells not only faces problems of cost and lifespan, but the use of hydrogen from a wide range of sources is also one of the key factors in its commercial application. Currently, less than 5% of the hydrogen produced in the world comes from water electrolysis (Gabriel B, Tiago A, Telmo L, et al. Int. J. Hydrogen Energy, 2020, 45: 7313-7338). The main method of industrial hydrogen production is to use coal, natural gas, and alcohols to reform hydrogen. The hydrogen produced in this way often contains some impurity gases, such as carbon monoxide (CO), hydrogen sulfide (H2S), carbon dioxide (CO2), trace ammonia (NH3), nitrogen (N2), etc. At the same time, different industrial by-product hydrogen also contains different impurity gases. However, the platinum-based catalysts used in hydrogen fuel cells are very easy to be poisoned. The most typical impurities in hydrogen are CO and H2S. Even a few ppm of CO or H2S can poison and deactivate the catalyst (St-Pierre J. Electrochim. Acta, 2010, (55): 4208-4211; Mohtadi R, Lee WK, Cowan S, et al. Electrochemical and Solid State Letters, 2003, 6 (12): A272-271). Developing poison-resistant catalysts is one of the most important strategies and methods for fuel cells to fully utilize the widespread source of hydrogen.
[0004] At present, PtRu alloy catalyst (Ianniello R, Schmidt VM, Stimming U, et al. Electrochimica Acta, 1994, 39 (11): 1863-1869; Yajima T, Uchida H, Watanabe M. J. Phys. Chem. B, 2004, 108: 2654-2659) is still the most classic and widely used catalyst for resisting CO poisoning. The most widely studied platinum alloy (PtM) catalysts include PtRu, PtCu, PtSn, PtOs, PtCo, PtW, PtMo, etc. For example, PtCu nanocubes (Xu D, Liu Z, Yang H, et al. Angew. Chem. Int. Ed, 2009, 48: 4217-4221), PtCu3 nanocages (BYXia, HBWu, X.Wang, XWLou. J. Am. Chem. Soc. 134 (2012) 13934-13937), PtMo alloy cluster catalysts PtMo10 / KB with single-atom Pt and single-atom Mo uniformly dispersed around (Jin CQ, Liao YC, Zhang A J, et al. Nano Energy, 2024, 122: 109305), Pt / RuMo / C (Oliveira AN, Egberto GF, Eliana MA, et al. Journal of the European Ceramic Society, 2003, 23 (15): 2987-2992), Fe 31 Pt 40 Ru 29 Ternary alloy catalysts (Wang D, Chou H, Lin Y, et al. J. Am. Chem. Soc, 2012, 134: 10011-10020) all showed good resistance to CO poisoning.
[0005] On the other hand, studies have shown that composite metal oxides can improve the resistance of catalysts to CO poisoning, such as RuSn-TiO2 catalysts (Ruixiang Wang, Xiamen University, 2020), reduced TiO2-loaded nano-Pt catalysts Pt / H-TiO2 (Han Jin, Zhiyou Zhou, Qiang Wang, J. Electrochemistry 20(2)(2014)6), CeO2 quantum dots mixed with commercial Pt / C to form CeO2-Pt / C-QDs (Hao Su, Wei Gao, Lanqing Li, Hongxing Yuan, Dan Wen, ACS Sustainable Chem. Eng. 11(2023)12317-12325), and MoO formed on the surface of PtMo alloy. x-1 Oxide layer catalyst PtMo / MoO x-1 / C (Heng Luo, Kai Wang, Fangxu Lin, Lv Fan, et al. Adv. Mater. 35 (29) (2023) 2211854). However, oxides have poor electronic conductivity, and most catalysts are mixed with carbon or loaded with oxides on carbon to improve the electronic conductivity of composite oxide catalysts.
[0006] Lopes et al. (Thiago Lopes, Valdecir A. Paganin, Ernesto R. Gonzalez, J. Power Sources 196 (2011) 6256-6263) and Eun-kyung Lee et al. (Eun-kyung Lee, et.al. Trans. Korean Hydrogen and New Energy Soc. 27 (6), 2016, 670-676) discussed the poisoning effect of H2S on fuel cells. There are currently few reports on catalysts that are resistant to H2S poisoning, and there are almost no reports on composite oxides that use the properties of oxides to improve the resistance of catalysts to H2S poisoning. Sun Shigang's team at Xiamen University proposed that coating a porous barrier layer on the catalyst surface can not only effectively improve the catalyst's resistance to CO poisoning, but also effectively improve the catalyst's resistance to H2S poisoning (Wang et al. Energy & Environmental Sci. 11 (2), 2018, 33-36; Wang et al. J am Chem Soc. 144 (21), 2022, 9292-9301). The selective oxidation of H2 is achieved through the steric hindrance effect, which is a universal anti-poisoning strategy.
[0007] The method of using a metal oxide composite conductive carrier not only improves the conductivity of the metal oxide composite catalyst, but also improves the anti-poisoning performance of the catalyst. Improving the uniformity of the dispersion of metal oxides on the conductive carrier is one of the key factors to further improve the anti-poisoning performance of the metal oxide composite catalyst. While preparing nano oxides, the present invention uniformly deposits the nano oxides on the surface of the nano conductive carrier in one step, which can achieve uniform dispersion of nano metal oxides on the conductive carrier and improve the conductivity of the composite carrier. In addition, different morphologies of oxides are loaded on the surface of the nano conductive carrier, which further improves the anti-poisoning performance of the catalyst. The catalyst not only shows good anti-CO poisoning performance, but also shows good anti-H2S poisoning performance. Summary of the invention
[0008] In view of the problems existing in the prior art, the object of the present invention is to provide a method for preparing a poisoning-resistant platinum-based fuel cell catalyst.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] A platinum-based catalyst for anti-poisoning, which is obtained by forming a composite carrier with a nano conductive carrier and an inorganic oxide, and then loading a noble metal and / or a noble metal alloy thereon;
[0011] In the catalyst, the proportion of precious metal is 10-70wt%; preferably 20-60wt%; more preferably 35-60wt%; the precious metal includes elements in the following group: Pt, Pd, Au, Ag, Ru;
[0012] In the composite carrier, the inorganic oxide accounts for 1-70wt%;
[0013] In some preferred embodiments, the noble metal is selected from any one or a combination of at least two of the following groups: Pt, Pd, Au, Ag, Ru;
[0014] The noble metal alloy is selected from PtM alloy; wherein, M is selected from transition metal; and M is selected from any one or a combination of at least two of the following groups: Fe, Co, Ni, Cu, Sn;
[0015] The noble metal alloy is also selected from any one of the following groups: PtPd alloy, PtAu alloy, PtAg alloy, PtRu alloy;
[0016] The nano conductive carrier is selected from conductive carbon with high specific surface area; preferably, the nano conductive carrier is selected from any one or a combination of at least two of the following groups: carbon black, acetylene black, graphite, graphene, carbon nanotubes;
[0017] More preferably, the nano-conductive carrier is selected from nano-conductive carriers with different doping; wherein the doped element is selected from any one or a combination of at least two of the following groups: N, P, S;
[0018] Such as any one or a combination of at least two selected from the following groups: N-doped nano-conductive carbon, P-doped nano-conductive carbon, S-doped nano-conductive carbon;
[0019] The inorganic oxide is selected from reducible oxides; preferably, the inorganic oxide is selected from any one or a combination of at least two of the following groups: titanium oxide, tin oxide, cerium oxide;
[0020] The morphology of the inorganic oxide is any one selected from the following group: nanoparticles, nanocubes, nanopolyhedrons, and nanorods.
[0021] In a second aspect, the present invention provides a method for preparing the platinum-based catalyst for anti-poisoning, comprising the following steps:
[0022] 1) using a one-step hydrothermal synthesis method to uniformly disperse the inorganic oxide on the nano-conductive carrier; after heat treatment, the nano-conductive carrier and the inorganic oxide are obtained to form a composite carrier;
[0023] 2) Depositing noble metals and / or noble metal alloys on the composite support.
[0024] In some preferred embodiments, the steps of the hydrothermal synthesis in step 1) are as follows:
[0025] 1-1) taking a salt solution corresponding to an inorganic oxide to obtain a solution A;
[0026] The solution A also includes a complexing agent containing nitrogen, and / or oxygen, and / or sulfur;
[0027] Preferably, the salt solution is selected from any one or a combination of at least two of the following groups: nitrate, chloride, acetate, sulfate;
[0028] The specific steps are: dissolving one or more of the nitrates, chlorides, acetates or sulfates of titanium, tin or cerium in water, and adding a complexing agent containing nitrogen and / or oxygen and / or sulfur to fully dissolve the complexes to obtain solution A.
[0029] 1-2) dispersing the nano-conductive carrier in an ethylene glycol aqueous solution to obtain a solution B;
[0030] The specific steps are: adding the nano-conductive carrier into the ethylene glycol aqueous solution, and mixing evenly by a method that can fully disperse, such as ultrasound, stirring, ball milling, or using several methods at the same time, to obtain solution B.
[0031] 1-3) After the above solution A and solution B are mixed evenly, they are added to an alkaline solution, such as sodium hydroxide or potassium hydroxide solution, under stirring conditions, or the alkaline solution is added to the mixed solution under stirring conditions, and after being fully dispersed and mixed evenly, they are transferred to a hydrothermal reaction kettle for hydrothermal reaction; the reaction product is washed with water and ethanol until the pH value is 6 to 8, preferably pH = 7;
[0032] 1-4) dispersing the nano-conductive carrier in an alkaline solution of ethylene glycol to obtain solution B;
[0033] The specific steps are as follows: adding the nano-conductive carrier to an ethylene glycol alkaline solution, wherein the alkali added is sodium hydroxide or potassium hydroxide, and mixing evenly by a method that can fully disperse, such as ultrasound, stirring, ball milling, or a combination of these methods, to obtain a solution C.
[0034] 1-5) adding solution C to the above solution A under stirring conditions, fully dispersing and mixing, and then transferring to a hydrothermal reaction kettle for hydrothermal reaction; washing the reaction product with water and ethanol until pH = 6 to 8, preferably pH = 7;
[0035] 1-6) heat-treating the product obtained in step 1-3) or 1-5) to obtain a composite carrier formed by the nano-conductive carrier and the inorganic oxide.
[0036] In some preferred embodiments, in step 1-1), the concentration of the salt solution is 0.001-1 mol / L.
[0037] In some preferred embodiments, in step 1-3), the concentration of the sodium hydroxide or potassium hydroxide solution is 0.01-25 mol / L, and the volume ratio of the alkali solution to the salt solution is 0.1-0.9.
[0038] In some preferred embodiments, in step 1-3), solutions A and B are mixed evenly and stirred for 0.1-2 hours, and then transferred into a hydrothermal reactor for reaction at 50-200° C. for 8-48 hours.
[0039] In some preferred embodiments, in step 1-4), the heat treatment temperature is 200-900° C., and the heat treatment time is 0.1-8 hours.
[0040] In a third aspect, the present invention also provides an application of the platinum-based catalyst in the anti-poisoning of anodes of fuel cells.
[0041] The beneficial effects of the present invention are:
[0042] The present invention adopts a one-step hydrothermal synthesis method, uses a complexing agent containing nitrogen, and / or oxygen, and / or sulfur, controls the nucleation and growth process of oxides, realizes uniform and highly dispersed deposition of oxides with different morphologies on a nano conductive carrier, and obtains a composite conductive carrier of composite oxides. On the composite carrier, a nano platinum or nano platinum alloy catalyst is loaded. The nano platinum or platinum alloy catalyst composited with oxides not only exhibits better catalytic activity for hydrogen oxidation reaction than commercial Pt / C, but also exhibits better resistance to CO and H2S poisoning. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a transmission electron microscopy image of CeO2 nanoparticles composite nanocarbon powder in Example 1;
[0044] Figure 2 HAADF diagram of the Pt / 10%CeO2-P / C catalyst prepared in Example 1 and element distribution diagram of Ce and Pt;
[0045] Figure 3 XRD pattern of the Pt / 10%CeO2-P / C catalyst prepared in Example 1;
[0046] Figure 4 This is a transmission electron microscopy image of CeO2 nanorod composite nano nitrogen-doped carbon prepared in Example 2;
[0047] Figure 5 This is a transmission electron microscopy image of the Pt / 60%CeO2-R / NC catalyst prepared in Example 2;
[0048] Figure 6 Comparison of the HOR performance of Pt / 40%CeO2-R / NC prepared in Example 2 and commercial Pt / C catalyst under 100ppmCO+H2 conditions in terms of CO poisoning resistance;
[0049] Figure 7 Comparison of the HOR performance of Pt / 40%CeO2-R / NC prepared in Example 2 and commercial Pt / C catalyst under 1ppmH2S+H2 condition;
[0050] Figure 8 Comparison of CO stripping results between Pt / 40%CeO2-R / NC prepared in Example 2 and commercial Pt / C catalyst;
[0051] Fig. 9 This is a transmission electron microscopy image of CeO2 nanocube composite nanocarbon powder prepared in Example 3;
[0052] Fig.10 This is the transmission electron microscopy image of the Pt / 40%CeO2-C / NC catalyst prepared in Example 3. DETAILED DESCRIPTION
[0053] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be emphasized that the following embodiments are merely illustrative and are not intended to limit the scope of the present invention and its application.
[0054] Example 1
[0055] Take 0.34 grams of conductive carbon powder XC72 and add it to a 30% ethylene glycol solution, and ultrasonicate for 3 hours. Dissolve 0.1 grams of cerium nitrate and 0.1 grams of EDTA-2Na in 10 milliliters of water, add to the above carbon powder solution, and stir thoroughly to mix evenly. Dissolve 1.2 grams of sodium hydroxide in a small amount of water, and add the sodium hydroxide solution dropwise to the above solution, stirring continuously for 30 minutes during the process. Add the above solution to a hydrothermal reactor and react at 100°C for 24 hours. Centrifuge, wash, and dry to obtain a composite carbon powder loaded with CeO2. The composite carbon powder is heat treated at 600°C under an inert atmosphere. The transmission electron microscope photograph of the composite carbon powder is shown below. Figure 1 As shown, CeO2 is nanoparticles, uniformly loaded on nanocarbon powder. The theoretical loading amount of CeO2 is about 10wt%.
[0056] The catalyst was obtained by using composite carbon powder as a carrier and depositing nano-platinum by a suitable method. The platinum loading was about 50wt%, and it was marked as Pt / 10%CeO2-P / C. The transmission electron microscope HADDF image and the element distribution map of Ce and Pt are shown in Figure 2 As shown in Figure 2, it can be seen that Ce and Pt are in the same position and are evenly dispersed on the carbon support. Figure 3 This is the XRD diagram of the Pt / 10%CeO2-P / C catalyst, where the peaks of Pt and CeO2 can be seen. Combining the transmission electron microscope image, element distribution diagram, and XRD results, it is shown that the CeO2 composite carbon carrier was successfully prepared and nano-platinum was successfully deposited on the carrier.
[0057] In the composite carbon support, similar results can be obtained when the CeO2 loading is 1wt% to 60wt% or more and the heat treatment temperature is 200-900℃.
[0058] Similar results can be obtained by replacing the conductive carbon powder XC72 with carbon nanotubes / doped carbon nanotubes, graphene / doped graphene, and N / P / S-doped carbon.
[0059] Example 2
[0060] Take 0.8 grams of nitrogen-doped carbon and add it to 65% ethylene glycol solution, and ultrasonicate for 3 hours. Dissolve 3 grams of cerium nitrate and 0.6 grams of EDTA-2Na in 10 milliliters of water, add to the above carbon powder solution, and stir thoroughly to mix evenly. Prepare 12 mol / L sodium hydroxide solution, and add the sodium hydroxide solution dropwise to the above solution, stirring continuously for 30 minutes during the process. Add the above solution to a hydrothermal reactor and react at 100°C for 24 hours. Centrifuge, wash, and dry to obtain a composite carbon powder loaded with CeO2. The composite carbon powder is heat treated at 600°C under an inert atmosphere. The transmission electron microscope photograph of the composite carbon powder is shown below. Figure 4 As shown in the transmission electron microscope image, it can be clearly seen that CeO2 is nanorods, which are uniformly loaded on the nanocarbon powder. The theoretical loading amount of CeO2 nanorods is about 60wt%.
[0061] The catalyst was obtained by using composite carbon powder as a carrier and depositing nano-platinum by a suitable method. The platinum loading was about 50wt%, and it was marked as Pt / 60%CeO2-R / C. Figure 5 As shown in Figure 2, it can be seen that nano-Pt is uniformly deposited on CeO2 nanorods and nitrogen-doped carbon supports.
[0062] In the composite carbon support, similar results can be obtained when the CeO2 loading is 1wt% to 60wt% or more and the heat treatment temperature is 200-900℃.
[0063] Similar results can be obtained by replacing nitrogen-doped carbon with conductive carbon powder, carbon nanotubes / doped carbon nanotubes, graphene / doped graphene, and P / S-doped carbon.
[0064] The HOR performance of the catalyst under hydrogen atmosphere was tested by the linear scanning method. The current density of Pt / 40%CeO2-R / NC and commercial Pt / C catalysts at 0.1V (vs.RHE) were 2.81mA / cm2 and 1.9mA / cm2, respectively, indicating that the catalytic activity of Pt / 40%CeO2-R / NC for hydrogen oxidation was significantly better than that of commercial Pt / C. At the same time, the hydrogen oxidation (HOR) performance of Pt / 40%CeO2-R / NC and commercial Pt / C catalysts at 0.1V (vs.RHE) was tested using hydrogen containing 100ppmCO and 1ppmH2S, respectively, and the chronoamperometric test was performed for 2 hours (7200s). The current retention rate of the HOR reaction can be used to evaluate the catalyst's resistance to CO and H2S poisoning. The comparison results of the resistance of Pt / 40%CeO2-R / NC and commercial Pt / C catalysts to CO and H2S poisoning are shown as follows: Figure 6 and Figure 7As shown in the figure, the HOR current retention rates of the Pt / 40%CeO2-R / NC catalyst in the chronoamperometric test for 2 hours in hydrogen containing 100ppmCO and 1ppmH2S are 63% and 82%, respectively, which are better than the 11% and 32% of commercial Pt / C.
[0065] Comparative Example 1
[0066] Literature (Heng Luo, Kai Wang, Fangxu Lin, Lv Fan, et al. Adv. Mater. 35 (29) (2023) 2211854) reported that MoO was formed on the surface of PtMo alloy. x-1 Oxide layer catalyst PtMo / MoO x-1 / C, in alkaline conditions 1MKOH, 100ppmCO+H2 atmosphere, the HOR current retention rate for 2500s is 88.5%. Figure 6 The results show that the HOR current retention rate of Pt / 40%CeO2-R / NC and commercial Pt / C catalysts in acidic conditions of 0.5MH2SO4 and 100ppmCO+H2 atmosphere for 2500s is 91%, which is better than that reported in the literature. At the same time, Pt / 40%CeO2-R / NC also has excellent resistance to H2S poisoning. In other words, compared with the literature, Pt / 40%CeO2-R / NC not only has better resistance to CO poisoning, but also has good resistance to H2S poisoning.
[0067] Comparative Example 2
[0068] The literature (Hao Su, Wei Gao, Lanqing Li, Hongxing Yuan, Dan Wen, ACS Sustainable Chem. Eng. 11 (2023) 12317-12325) reported that the catalyst CeO2-Pt / C-QDs formed by mixing CeO2 quantum dots and commercial Pt / C can effectively improve the performance of methanol oxidation under alkaline conditions, and compared the performance of CO oxidation under acidic conditions (CO stripping experiment). The onset potential of CO oxidation and the amount of negative shift of the peak potential in the CO stripping experiment can evaluate the catalyst's resistance to CO poisoning. The more negative the potential shift, the better the catalyst's resistance to CO poisoning. The COstripping experiment reported in the literature showed that the CO oxidation onset potential of CeO2-Pt / C-QDs was 82 mV negatively shifted compared to commercial Pt / C. Figure 8The CO stripping experimental results of Pt / 40%CeO2-R / NC and commercial Pt / C catalysts are shown. It can be seen that the CO oxidation onset potential of Pt / 40%CeO2-R / NC is 269mV negatively shifted compared with the commercial Pt / C catalyst, and the peak potential is 48mV negatively shifted, which is significantly better than the performance of the catalyst using the same composite CeO2 reported in the literature.
[0069] Example 3
[0070] Take 1.8 grams of nitrogen-doped carbon, add it to ethylene glycol, and ultrasonicate for 3 hours. Dissolve 3 grams of cerium nitrate and 0.04 grams of EDTA-2Na in 10 milliliters of water, add to the above carbon powder solution, and stir thoroughly to mix evenly. Prepare 20 mol / L sodium hydroxide solution and add it dropwise to the above solution, stirring continuously for 30 minutes during the process. Add the above solution to a hydrothermal reactor and react at 180°C for 24 hours. Centrifuge, wash, and dry to obtain a composite carbon powder loaded with CeO2. The composite carbon powder is heat treated at 600°C under an inert atmosphere. The transmission electron microscope photograph of the composite carbon powder is shown below. Fig. 9 CeO2 is nanocubes with a particle size of 10-20 nanometers, uniformly loaded on nanocarbon powder. The theoretical loading of CeO2 nanocubes is about 40wt%
[0071] The catalyst was obtained by using composite carbon powder as a carrier and depositing nano-platinum by a suitable method. The platinum loading was about 50wt%, and it was marked as Pt / 40%CeO2-C / NC. Fig.10 As shown in Figure 2, it can be seen that nano-Pt is uniformly deposited on CeO2 nanocubes and nitrogen-doped carbon supports.
[0072] In the composite carbon support, similar results can be obtained when the CeO2 loading is 1wt% to 60wt% or more and the heat treatment temperature is 200-900℃.
[0073] Similar results can be obtained by replacing nitrogen-doped carbon with conductive carbon powder, carbon nanotubes / doped carbon nanotubes, graphene / doped graphene, and P / S-doped carbon.
[0074] The hydrogen oxidation (HOR) performance of Pt / 40%CeO2-C / NC and commercial Pt / C catalysts at 0.1V (vs.RHE) was tested in hydrogen containing 100ppmCO and 1ppmH2S, respectively, and the chronoamperometric test was performed for 2 hours (7200s). The current retention rate of the HOR reaction can be used to evaluate the catalyst's resistance to CO and H2S poisoning. The HOR current retention rates of the Pt / 40%CeO2-C / NC catalyst in hydrogen containing CO and H2S were 32% and 53%, respectively, which are better than the 11% and 32% of commercial Pt / C.
[0075] The CeO2 composite carbon carrier prepared above can be loaded with other platinum-based alloy catalysts by using a suitable platinum-based alloy catalyst preparation method to further improve the activity and anti-poisoning performance of the catalyst, such as platinum-copper, platinum-tin, platinum-cobalt, platinum-iron, platinum-nickel, platinum-ruthenium, platinum-palladium, platinum-silver, and platinum-gold alloys.
[0076] Example 4
[0077] Take 1.8 grams of high specific surface area conductive carbon black BP2000, add it to ethylene glycol, and ultrasonicate for 3 hours. Dissolve 1.55 grams of cerium chloride, 0.21 grams of tin chloride and 0.3 grams of sodium citrate in 20 milliliters of water, add it to the above carbon powder solution, and stir it thoroughly to mix evenly. Prepare 25 mol / L sodium hydroxide solution and add it dropwise to the above solution, stirring continuously for 30 minutes during the process. Add the above solution to a hydrothermal reactor and react at 100°C for 24 hours. Centrifuge, wash and dry to obtain composite carbon powder. Heat treat the composite carbon powder at 400°C under an inert atmosphere to obtain Ce x Sn y O2 composite carbon powder, wherein the theoretical loading amount of oxide is about 40wt%. The composite carbon powder is used as a carrier, and nano-platinum is deposited by a suitable method to obtain a catalyst, wherein the platinum loading amount is about 10wt%.
[0078] Example 5
[0079] Take 0.8 g of nitrogen-doped carbon, add it to ethylene glycol, and ultrasonicate for 3 hours. Dissolve 1.99 g of cerium acetate, 0.18 g of titanium chloride and 0.04 g of EDTA-2Na in 20 ml of water, add to the above carbon powder solution, and stir thoroughly to mix. Prepare 15 mol / L sodium hydroxide solution and add it dropwise to the above solution, stirring continuously for 30 minutes. Add the above solution to a hydrothermal reactor and react at 100°C for 24 hours. Centrifuge, wash and dry to obtain composite carbon powder. Heat treat the composite carbon powder at 800°C under an inert atmosphere to obtain Ce x Ti y O2 composite carbon powder, wherein the theoretical loading amount of oxide is about 60wt%. The composite carbon powder is used as a carrier, and nano-platinum is deposited by a suitable method to obtain a catalyst, wherein the platinum loading amount is about 60wt%.
[0080] Example 6
[0081] Take 4.8 grams of graphene, add it to 80% ethylene glycol aqueous solution, and ultrasonicate for 3 hours. Dissolve 1.8 grams of stannous chloride and 0.4 grams of urea in 20 milliliters of water, add it to the above carbon powder solution, and stir and mix well. Prepare 10 mol / L sodium hydroxide solution and add it dropwise to the above solution, stirring continuously for 30 minutes during the process. Add the above solution to a hydrothermal reactor and react at 100°C for 24 hours. Centrifuge, wash and dry to obtain composite carbon powder. Heat treat the composite carbon powder at 300°C under an inert atmosphere to obtain SnO2 composite carbon powder, in which the theoretical loading of the oxide is about 20wt%. Using the composite carbon powder as a carrier, a catalyst is obtained by depositing nano-platinum using a suitable method, and the platinum loading is about 35wt%.
[0082] Example 7
[0083] Take 4.8 grams of nitrogen-doped graphene, add it to 50% ethylene glycol, and ultrasonicate for 1 hour. Prepare 10 mol / L sodium hydroxide solution, add it to the above solution, and ball mill for 1 hour to obtain a carbon powder solution. Dissolve 0.3 grams of titanium tetrachloride and 0.005 grams of thiourea in 20 milliliters of water and stir well to mix. Add the titanium tetrachloride solution to the above carbon powder solution and continue stirring for 30 minutes during the process. Add the above solution to a hydrothermal reactor and react at 100°C for 24 hours. Centrifuge, wash, and dry to obtain a composite carbon powder. Heat treat the composite carbon powder at 200°C under an inert atmosphere to obtain TiO 2-x The composite carbon powder has a theoretical loading of about 4.5 wt% of oxide. The composite carbon powder is used as a carrier and nano-platinum is deposited by a suitable method to obtain a catalyst, wherein the platinum loading is about 40 wt%.
[0084] Example 8
[0085] Take 0.8 g of carbon nanotubes, add it to 50% ethylene glycol, and ultrasonicate for 3 hours. Dissolve 1.5 g of cerous sulfate, 0.18 g of stannous chloride and 0.08 g of thiourea in 20 ml of water, add it to the above carbon powder solution, and stir it thoroughly to mix evenly. Prepare 5 mol / L sodium hydroxide solution. Add the carbon powder mixed solution to the sodium hydroxide solution, and stir continuously for 30 minutes during the process. Add the above solution to a hydrothermal reactor and react at 100°C for 24 hours. Centrifuge, wash and dry to obtain composite carbon powder. Heat treat the composite carbon powder at 600°C under an inert atmosphere to obtain Ce x Sn y O2 composite carbon powder, wherein the theoretical loading amount of oxide is about 40wt%. The composite carbon powder is used as a carrier, and nano-platinum is deposited by a suitable method to obtain a catalyst, wherein the platinum loading amount is about 20wt%.
Claims
1. A platinum-based catalyst for anti-poisoning, which is obtained by forming a composite carrier with a nano-conductive carrier and an inorganic oxide, and then loading a noble metal and / or a noble metal alloy thereon; In the catalyst, the proportion of precious metal is 10-70wt%; preferably 20-60wt%; more preferably 35-60wt%; In the composite carrier, the inorganic oxide accounts for 1-70wt%; The noble metal is selected from any one or a combination of at least two of the following groups: Pt, Pd, Au, Ag, Ru; The noble metal alloy is selected from PtM alloys; wherein, The M is selected from transition metals; the M is selected from any one or a combination of at least two of the following groups: Fe, Co, Ni, Cu, Sn; The noble metal alloy is also selected from any one of the following groups: PtPd alloy, PtAu alloy, PtAg alloy, PtRu alloy; The nano conductive carrier is selected from conductive carbon with high specific surface area; preferably, the nano conductive carrier is selected from any one or a combination of at least two of the following groups: carbon black, acetylene black, graphite, graphene, carbon nanotubes; More preferably, the nano-conductive carrier is selected from nano-conductive carriers with different doping; wherein the doped element is selected from any one or a combination of at least two of the following groups: N, P, S; Such as any one or a combination of at least two selected from the following groups: N-doped nano-conductive carbon, P-doped nano-conductive carbon, S-doped nano-conductive carbon; The inorganic oxide is selected from reducible oxides; preferably, the inorganic oxide is selected from any one or a combination of at least two of the following groups: titanium oxide, tin oxide, cerium oxide; The morphology of the inorganic oxide is any one selected from the following group: nanoparticles, nanocubes, nanopolyhedrons, and nanorods.
2. A method for preparing a platinum-based catalyst for anti-poisoning according to claim 1, comprising the following steps: 1) using a one-step hydrothermal synthesis method to uniformly disperse the inorganic oxide on the nano-conductive carrier; after heat treatment, the nano-conductive carrier and the inorganic oxide are obtained to form a composite carrier; 2) Depositing noble metals and / or noble metal alloys on the composite support.
3. The method for preparing a platinum-based catalyst resistant to poisoning according to claim 2, wherein the hydrothermal synthesis step in step 1) is as follows: 1-1) taking a salt solution corresponding to an inorganic oxide to obtain a solution A; The solution A also includes a complexing agent containing nitrogen, and / or oxygen, and / or sulfur; Preferably, the salt solution is selected from any one or a combination of at least two of the following groups: nitrate, chloride, acetate, sulfate; The specific steps are: dissolving one or more of nitrates, chlorides, acetates or sulfates of titanium, tin or cerium in water, adding a complexing agent containing nitrogen and / or oxygen and / or sulfur, and fully dissolving them to obtain solution A. 1-2) dispersing the nano-conductive carrier in an ethylene glycol aqueous solution to obtain a solution B; The specific steps are: adding the nano-conductive carrier into the ethylene glycol aqueous solution, and mixing evenly by a method that can fully disperse, such as ultrasound, stirring, ball milling, or using several methods at the same time, to obtain solution B. 1-3) After the above solution A and solution B are mixed evenly, they are added to an alkaline solution, such as sodium hydroxide or potassium hydroxide solution, under stirring conditions, or the alkaline solution is added to the mixed solution under stirring conditions, and after being fully dispersed and mixed evenly, they are transferred to a hydrothermal reaction kettle for hydrothermal reaction; the reaction product is washed with water and ethanol until the pH value is 6 to 8, preferably pH = 7; 1-4) dispersing the nano-conductive carrier in an alkaline solution of ethylene glycol to obtain solution B; The specific steps are as follows: adding the nano-conductive carrier to an ethylene glycol alkaline solution, wherein the alkali added is sodium hydroxide or potassium hydroxide, and mixing evenly by a method that can fully disperse, such as ultrasound, stirring, ball milling, or a combination of these methods, to obtain a solution C. 1-5) adding solution C to the above solution A under stirring conditions, fully dispersing and mixing, and then transferring to a hydrothermal reaction kettle for hydrothermal reaction; washing the reaction product with water and ethanol until pH = 6 to 8, preferably pH = 7; 1-6) heat-treating the product obtained in step 1-3) or 1-5) to obtain a composite carrier formed by the nano-conductive carrier and the inorganic oxide.
4. The method for preparing a platinum-based catalyst resistant to poisoning according to claim 3, wherein in step 1-1), the concentration of the salt solution is 0.001-1 mol / L.
5. The method for preparing a platinum-based catalyst resistant to poisoning according to claim 3, wherein in the steps 1-3), the concentration of the sodium hydroxide or potassium hydroxide solution is 0.01-25 mol / L, and the volume ratio of the alkali solution to the salt solution is 0.1-0.
9.
6. The method for preparing a platinum-based catalyst for resistance to poisoning according to claim 3, wherein in the step 1-3), solutions A and B are mixed evenly and stirred for 0.1-2 hours, and then transferred into a hydrothermal reactor and reacted at 50-200°C for 8-48 hours.
7. The method for preparing a platinum-based catalyst resistant to poisoning according to claim 3, wherein in the steps 1-4), the heat treatment temperature is 200-900°C and the heat treatment time is 0.1-8 hours.
8. Use of the platinum-based catalyst according to claim 1 in anti-poisoning of anodes of fuel cells.